Eritrograma, relação viscerosomática, hepatosomática e esplenosomática em tainhas Mugil platanus Günther (Osteichthyes, Mugilidae) parasitadas - Ranzani-paiva, Maria José Tavares [UNESP]; Tavares-dias, Marcos (Sociedade Brasileira de Zoologia, 2002)
The present work describes mean values of hepatosomatic relation (HSR), splenosomatic relation (SSR) and viscerosomatic relation (VSR) in mullet, Mugil platanus Günther, 1880 (Mugilidae) from Cananéia lagoon-stuarine region, São Paulo, Brazil. Parasites of the following taxonomic categories were found in the respective organs - gills: Monogenean helminths, Trichodinidae, Copepoda and Hirudinea; blood: Haemogregarina mugili Carini, 1932 (Apicomplexa) e Trypanosoma froesi Lima, 1976 (Sarcomastigophora) and liver: cysts of Phagicola sp. The average values of red blood cells count (RBC), hemoglobin rate (Hb), mean corpuscular volume (MCV), mean corpuscular hemoglobin concentration (MCHC) of male, female and indifferentiaed, were similar. However, the hematocrit (Hct) in male was higher than female and indifferentiaed. It was not observed significant differences in HSR, SSR and VSR between male and female. Nervertheless, the VSR in indifferentiaed mullet was higher than for male and female.
Erythrogram, hepatosomatic, splenosomatic and viscerosomatic relation in mullet, Mugil platanus Günther (Osteichthyes, Mugilidae) parasitized
Keywords: Mugil platanus; erithrocytes; hepatosomatic relation; splenosomatic relation; viscerosomatic relation; parasites